When calls the heart. Year 10 : collector's edition [videorecording (DVD)] - Tinker, John, 1958-; Thompson, Derek (Screenwriter); Stewart, Elizabeth Mary; Devereaux, Allie; Krakow, Erin; Hutton, Pascale; Wagner, Jack, 1959-; Smith, Kavan, 1970-; McNally, Chris, 1988-; McGarry, Kevin, 1985-; Brooks, Andrea, 1989-; Leacock, Viv, 1974-; et al. (Edify Films, 2023)
When Elizabeth leaves her comfortable life in the city to move to a frontier town, she finds new purpose and love.